Pollen morphological characters variation among species of Strobilanthes s.l. from Sumatra, Indonesia and its taxonomic implications - SURATMAN SURATMAN; SURANTO SURANTO; MUZZAZINAH MUZZAZINAH; PURNOMO PURNOMO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Suratman, Suranto, Muzzazinah, Purnomo. 2022. Pollen morphological characters variation among species of Strobilanthes s.l. from Sumatra, Indonesia and its taxonomic implications. Biodiversitas 23: 4636-4648. The objective of this study was to evaluate pollen morphological characters variation and its taxonomic value among species of Strobilanthes s.l. from Sumatra. A total of 32 species from four genera previously recognized within the subtribe Strobilanthineae were used for pollen morphology observations using Light Microscope (LM) and Scanning Electron Microscope (SEM). A total of ten pollen morphological characters (both quantitative and qualitative) were observed in this study. In general, a great variation occurs in the majority of investigated pollen morphological characters. A similarity dendrogram among species of Strobilanthes s.l. based on pollen morphological character data revealed two major clusters. Cluster I consist of 25 species that differed from species in Cluster II in having pollen type I, pollen type II and pollen type III with a similarity coefficient of 0.61. Cluster II consists of seven species and has pollen type IV, pollen type V, pollen type VI and pollen type VII with a similarity coefficient of 0.46. An identification key to the species of Strobilanthes s.l. based on pollen morphology is also established for easy discrimination of the investigated taxa. This study revealed that pollen morphology was taxonomically useful character for identification and taxa delimitation of Strobilanthes s.l., especially at the species level. The results of this study also support earlier works through molecular studies, statistical analysis, gross morphology observations and leaf anatomy studies that all segregate genera of the subtribe Strobilanthinae should be merged under a single and well-defined genus as Strobilanthes s.l.